CHILD MORTALITY: ASSESSMENT OF THE REDE MÃE PARANAENSE PROGRAM AT A REGIONAL HEALTH DISTRICT IN THE STATE OF PARANÁ - Amanda Netto; Rosane Meire Munhak da Silva; Marieta Fernandes Santos; Mauren Teresa Grubisich Mendes Tacla; Sebastião Caldeira; Sheila Cristina Rocha Brischiliari (Universidade Federal do Paraná, 2017)
The objective was to analyze childhood mortality at a regional health department in the State of Paraná before and after the implementation of the Rede Mãe Paranaense program. The descriptive and retrospective method was used with secondary data from the Information System of the State Secretary of Health, using data from children younger than one year and causes of death, between 2009 and 2014. It was observed that, in the early neonatal period, the population size increased from 15,000 to 50,000, from 31% to 36% of deaths after the implementation. Despite the implementation of the program to improve women's health during pregnancy and birth and infant health, the avoidable deaths remained high, i.e. 63% before and 51% after the implementation. The results did not evidence a significant reduction in childhood mortality after the implementation of the program, but its implementation is still recent, demanding further time for the cities to adapt to the program and invest in the training of the professionals involved